Subgrade Stabilization Assessment Of Kuantan Clay Using Lime, Portland Cement, Fly Ash, And Bottom Ash - Achmad Fauzi, Abdul Wahab; Wan Mohd Nazmi, Wan Abdul Rahman (2011)
This paper proposes an assessment of the utilization of lime, Portland cement (PC), fly ash and bottom ash as stabilizer of soft sub grades material in highway construction. The research conducts various contents of lime, PC, fly ash and bottom ash to different types of clay soils from various sites in Kuantan. The compaction tests and California Bearing Ratio (CBR) tests were applied in soil samples to estimate the optimum mixture design. The samples were set up by mixing soil samples with various content of lime, PC, fly ash and bottom ash at different water content. The accomplishment of sub-grade stabilization depends on the engineering properties of soils and characteristic of additives. The laboratory result shows that the strength gain in stabilization mainly depends on two factors: additives content and molding water content. The variation content of lime, PC, fly ash and bottom ash were 4%, 8% and 12% by total weight.